Priorities for Mediterranean marine turtle conservation and management in the face of climate change. (1st August 2023) - Mazaris, Antonios D.; Dimitriadis, Charalampos; Papazekou, Maria; Schofield, Gail; Doxa, Aggeliki; Chatzimentor, Anastasia; Turkozan, Oguz; Katsanevakis, Stelios; Lioliou, Aphrodite; Abalo-Morla, Sara; Aksissou, Mustapha; Arcangeli, Antonella; et al.
Abstract: As climate-related impacts threaten marine biodiversity globally, it is important to adjust conservation efforts to mitigate the effects of climate change. Translating scientific knowledge into practical management, however, is often complicated due to resource, economic and policy constraints, generating a knowledge-action gap. To develop potential solutions for marine turtle conservation, we explored the perceptions of key actors across 18 countries in the Mediterranean. These actors evaluated their perceived relative importance of 19 adaptation and mitigation measures that could safeguard marine turtles from climate change. Of importance, despite differences in expertise, experience and focal country, the perceptions of researchers and management practitioners largely converged with respect to prioritizing adaptation and mitigation measures. Climate change was considered to have the greatest impacts on offspring sex ratios and suitable nesting sites. The most viable adaptation/mitigation measures were considered to be reducing other pressures that act in parallel to climate change. Ecological effectiveness represented a key determinant for implementing proposed measures, followed by practical applicability, financial cost, and societal cost. This convergence in opinions across actors likely reflects long-standing initiatives in the Mediterranean region towards supporting knowledge exchange in marine turtle conservation. Our results provide important guidance on how to prioritize measures that incorporate climate change in decision-making processes related to the current and future management and protection of marine turtles at the ocean-basin scale, and could be used to guide decisions in other regions globally. Importantly, this study demonstrates a successful example of how interactive processes can be used to fill the knowledge-action gap between research and management. Highlights: Knowledge-action gap on marine turtle conservation under climate change was explored. Researchers and conservation managers from 18 Mediterranean countries participated. Participant perceptions largely converged despite different expertise or experience. The risk to hatchling sex ratios and loss of suitable nesting sites were highlighted. Legislative actions ranked scores regarding support to adaptation/mitigation measures.